On GIT quotients of the symplectic group, stability and bifurcations of periodic orbits (with a view towards practical applications) - Frauenfelder, Urs; Moreno, Agustin (The journal of symplectic geometry, 2023)
International Press of Boston - publishers of scholarly mathematical and scientific journals and books